respon pertumbuhan dan hasil buncis akibat pemberian bokasi kulit pisang dan fosfat pada tanah aluvial - nopebrianti, yati; susana, rini; abdurrahman, tatang (Jurnal Sains Pertanian Equator, 2017)
ABSTRACT This study aims to determine the dose of banana skin and phosphate fertilizers as well as their interactions that provide the best growth and yield of cammon bean on alluvial. Research was conducted at Swadaya Street, Kubu Raya Regency, West Kalimantan Province, from February 18th, 2017 to April 20, 2017. This research uses Factorial Complete Random Design. The first factor of banana skin boashi (10,20,and 30 ton/ha) and the second factor was the dose of P (230,280 and 330)kg/ha). The variables observed in this study were flowering age, root volume, dry weight of plants, number of pods per plant and weight of pods per plant. The results showed that bokashi made of banana skin with dose of 30 tons /ha showed the best result on flowering age, root volume, and dry weight of plant. Phosphate application has not been able to increase the growth and yield of ccammon beans. There is no interaction between bokashi made of banana skin and phosphate in all observation variables. Keywords: alluvial, bokashi, phosphate, cammon bean.